Cumulative evidence for relationships between multiple variants in 8q24 and colorectal cancer incidence. Issue 35 (August 2018) - Tong, Yu; Wang, Huiqing; Li, Shiping; Zhao, Fengyan; Ying, Junjie; Qu, Yi; Mu, Dezhi
Abstract : Abstract: Genome-wide association studies (GWAS) have identified multiple independent cancer susceptibility loci at chromosome 8q24. We conducted a comprehensive research synopsis and meta-analysis to evaluate associations between 6 variants in 8q24 and risk of colorectal cancer using data from 31 eligible articles totaling 41, 942 cases and 49, 968 controls. Of the 6 variants located in 8q24, 3 were significantly associated with risk of colorectal cancer. In particular, both homozygous TT and heterozygous CT genotypes of rs10505477, as well as the GG and TG genotypes of rs6983267, were associated with risk of colorectal cancer. Our study provides summary evidence that common variants in the 8q24 are associated with risk of colorectal cancer in this large-scale research synopsis and meta-analysis. Further studies are needed to explore the exact role of the variants in the 8q24 involved in the etiology of colorectal cancer.